Active control or passive control? (Outline of active noise control and it's application to practical problems) - Ken'iti KIDO (Archives of Acoustics)
This paper overviews the history, the principle and some key technologies of the active noise control and points out that the passive control should be incorporated with the active control to improve the annoyance of noise. That is, the suppression of higher frequency noise by the passive method should be jointly used with the active control. There are feed forward method and feed back method in the active control system, but this paper concerns with the feed forward method only as the stability is important. This paper concentrates the technology using FIR filter, and the renewal algorithm of the coefficients of FIR adaptive filter is shown in unified form. Next, the relation between the arrangement of additional sound source and the reduction of noise radiation is given according to the numerical computation and the control of power transformer noise is briefly explained as a practical example carried out by the author. Finally, the change in A-weighted noise level and the sound quality in hearing by the ANC is discussed.